2022
DOI: 10.1007/s11033-022-08029-1
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genomes of Crispatotrochus rubescens and Crispatotrochus rugosus (Hexacorallia; Scleractinia): new insights on the phylogeny of the family Caryophylliidae

Abstract: Background Caryophylliidae is one of the most diverse scleractinian families, however it was recovered as polyphyletic in multiple molecular studies. Recently, the mitochondrial gene order was proposed as a character for a taxonomic revision of the family. Here we describe the rst mitogenome of the caryophylliid genus Crispatotrochus, whose phylogenetic position remains uncertain. Methods and resultsThe complete mitochondrial genomes of Crispatotrochus rubescens and Crispatotrochus rugosus were sequenced, asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…More recently, the more thorough usage of high‐throughput sequencing methods—for example target enrichment and genome skimming—has enabled the access and handling of vast amounts of molecular data (Goodwin et al., 2016; Kulkarni & Frommolt, 2017; Quattrini et al., 2023). Coupling nuclear ultraconserved elements (UCEs) and exon loci and complete mitochondrial (mt) genomes, a recent study showed that all sequenced components of the caryophylliid clade comprising the type genus of the family (i.e., Caryophyllia Lamarck, 1801), have a specific mt genome rearrangement (i.e., a transposition of the gene block containing cob , nad2 and nad6 genes between nad5 5′ and trnW different from the canonical scleractinian mt gene order—gene block located between nad1 and atp6 ) not present in any other sequenced scleractinian taxa (Seiblitz et al., 2022; Vaga et al., 2022). The aforementioned studies recovered the genera Crispatotrochus Tenison‐Woods, 1878, Desmophyllum Ehrenberg, 1834, Premocyathus Yabe & Eguchi, 1942 and Solenosmilia Duncan, 1873 grouping with Caryophyllia in a monophyletic clade that is phylogenetically independent from all the other ‘caryophylliid’ clades recovered so far.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the more thorough usage of high‐throughput sequencing methods—for example target enrichment and genome skimming—has enabled the access and handling of vast amounts of molecular data (Goodwin et al., 2016; Kulkarni & Frommolt, 2017; Quattrini et al., 2023). Coupling nuclear ultraconserved elements (UCEs) and exon loci and complete mitochondrial (mt) genomes, a recent study showed that all sequenced components of the caryophylliid clade comprising the type genus of the family (i.e., Caryophyllia Lamarck, 1801), have a specific mt genome rearrangement (i.e., a transposition of the gene block containing cob , nad2 and nad6 genes between nad5 5′ and trnW different from the canonical scleractinian mt gene order—gene block located between nad1 and atp6 ) not present in any other sequenced scleractinian taxa (Seiblitz et al., 2022; Vaga et al., 2022). The aforementioned studies recovered the genera Crispatotrochus Tenison‐Woods, 1878, Desmophyllum Ehrenberg, 1834, Premocyathus Yabe & Eguchi, 1942 and Solenosmilia Duncan, 1873 grouping with Caryophyllia in a monophyletic clade that is phylogenetically independent from all the other ‘caryophylliid’ clades recovered so far.…”
Section: Introductionmentioning
confidence: 99%